Flat electroencephalography’s cluster centers movement tracking during epileptic seizure - Mukhni, Syu’aiba; Tan, Lit Ken; Nor Azwadi, Che Sidik; Goh, Chien Yong; Lee, Kee Quen; Chuan, Zun Liang; Asako, Yutaka (American Institute of Physics Inc., 2018)
Epilepsy is a term used for a chronic disorder caused by excessive and abnormal nerve cell activity within the brain. This dynamic process is often associated with electroencephalography (EEG), which is an electrophysical method to record the electrical activity of the brain. For epilepsy patients, their EEG signals are characterized by abnormal signal flow and large spikes. This shows the excessive electrical activity within the brain can be extracted thus locating problematic cells of epilepsy is possible. However, it is very challenging due to the complexity of the signals to be analyzed. Through fEEG, the signals can be viewed in a Cartesian plane which consists of EEG’s channels and cluster center of electrical potential during epilepsy. To date, no research has been done on across time-frame of fEEG. In order to gain better insight into the dynamic process of epilepsy, a dynamic study on the cluster center movement across time-frame is necessary. Therefore, this study to shows the tracking of cluster centers movements across time-frame of fEEG. This movement tracking is essentials to understand the behavior of epilepsy such as the patterns of electrical potential. Further studies on the model could potentially assist in locating the problematic cells caused by epilepsy.